Alterations in Respiratory Mechanics and Neural Respiratory Drive After Restoration of Spontaneous Circulation in a Porcine Model Subjected to Different Downtimes of Cardiac Arrest. Issue 19 (1st October 2019) - Yang, Zhengfei; Zheng, Houzhen; Lin, Lin; Hou, Jingying; Wen, Cai; Wang, Yue; Ling, Qin; Jiang, Longyuan; Tang, Wanchun; Chen, Rui
Abstract : Background: The potential alterations of respiratory pathophysiology after cardiopulmonary resuscitation (CPR) are relatively undefined. While untreated arrest is known to affect post–cardiopulmonary resuscitation circulation, whether it affects respiratory pathophysiology remains unclear. We aimed to investigate the post–cardiopulmonary resuscitation changes in respiratory mechanics and neural respiratory drive with varying delays (5 or 10 minutes) in the treatment of ventricular fibrillation (VF). Methods and Results: Twenty‐six male Yorkshire pigs were used. Anesthetized pigs weighing 38±5 kg were randomized into 3 groups (n=10 each in the VF5 and VF10 groups, with VF kept untreated for 5 and 10 minutes, respectively, and n=6 in the sham group without VF). Defibrillation was attempted after 6 minutes of cardiopulmonary resuscitation. Pulse‐induced contour cardiac output, respiratory mechanics, diaphragmatic electromyogram, blood gas, lung imaging, and histopathology were evaluated for 12 hours. Significantly elevated mean root mean square of diaphragmatic electromyogram, transdiaphragmatic pressure, and minute ventilation were observed, but reduced minute ventilation/mean root mean square, dynamic pulmonary compliance, and Pao 2 were noted in both VF groups. Despite recovery of spontaneous breathing, the abnormalities in respiratory mechanics and neural respiratory drive, Pao 2, and extravascular lung water continued to last for >12 hours. The changes in imaging ( P =0.027) and histopathology ( P =0.012) were more severe in the VF10 group compared with the VF5 group. Conclusions: There is an uncoupling between the respiratory center and ventilation after restoration of spontaneous circulation. Prolonged untreated arrest from cardiac arrest contributes to more serious alterations in lung pathophysiology.